Indianité et lutte des classes - Herbert, Jean-Loup; Bockler, Carlos Guzman; Quan, Julio (Paris: Union générale d'éditions, 1972)
"par Jean-Loup Herbert, Carlos Guzman Bockler, Julio Quan Bibliotheek François Vercammen"